HRM and organizational innovation- A literature review - K, sreeja (IJRDO - Journal of Business Management, 2018)
Innovation is a key element in an organization’s success. Only those organizations which are ready to innovate can survive in today’s competitive environment. Introducing innovation or change is one of the biggest challenges that organizational leaders face. People naturally are reluctant to change. There will be many people in an organization who does not want to change from the usual way of doing things. HR managers play a vital role in introducing innovation in an organization with the acceptance of people. This paper is a review of existing literature about the relationship between HRM and organizational innovation.